A teoria kantiana do agir racional - Fernandes, Darley Alves (2015)
Our goal in this work will be to offer a perspective of understanding the problem freedom of the will and, respectively, a possible solution to the question from the Critique of pure reason. In this sense, we will seek to define the problem of freedom of the will as a problem concerning the legislation of act which lead us to ask what are the rules, causes and norms governing human act. What are the laws and causes of human action? Are the natural laws and causes, desires and inclinations, or are the laws and rational motives, practical principles? We are interested in defending the notion of free rational act presuppose, on the one hand, a practical reason that guides the action from prescription that command and impose normative authority and, on the other hand, the practical-deliberative ability of the agent to recognize and judging such prescriptions. All discussion is throughout by the concept of free choice (practical freedom). Therefore, we will investigate exhaustively the characteristics of this concept, the structure, spontaneity, relation with other faculties, and so on. Overall, the conception of free will that we will defend depends, at first, of spontaneity and self- determination capacity of free choice face the sensible inclinations. We get the concept of will (Wille) from an explanation of the reflective characteristics of free choice and faculty of desire, that is, the concept of will arises as necessary to the concept of free choice. By free will we must understanding the human ability to act through representation of laws and practical-rational principles, the ability of self-determination of the desire by means practical reason overcoming of inclinations by the possibility of acting on a pure rational motive. At the end we will see that freedom of the will defense provides us with a fruitful theory of action.